A rational strategy to support approved COVID-19 vaccines prioritization - Javier Burgos-Salcedo (Taylor & Francis Group, 2021)
The World Health Organization (WHO) proposed a set of criteria to be considered for the prioritization of COVID-19 candidate vaccines for further development of phase II/III clinical trials, thinking in a target audience that includes vaccine scientists, product developers, manufacturers, regulators, and funding agencies. In this paper, a knowledge-based or rational strategy is employed to perform a prioritization matrix of approved COVID-19 vaccines: BBIBP-CorV, JANSSEN, CORONAVAC, SPUTNIK V, MODERNA, PFIZER, and VAXZEVRIA, based on those proposed criteria by WHO, related to safety, efficacy, stability, implementation, and availability. We found that JANSSEN vaccine is the one with the highest score in the present study, but our analysis suggests that the WHO criteria could be more useful if they are considered separately, taking into account the social, demographic and economic characteristics of each country.